2014
DOI: 10.1038/bjc.2014.277
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein level is a prognostic indicator for survival and improves the predictive ability of the R-IPI score in diffuse large B-cell lymphoma patients

Abstract: Background:High levels of C-reactive protein (CRP), an acute phase protein, proofed being associated with decreased clinical outcome in small-scale studies in diffuse large B-cell lymphoma (DLBCL). The aim of this study was to evaluate the prognostic impact of pretreatment CRP levels on overall survival (OS) and disease-free survival (DFS) in a large bicentre study of DLBCL patients.Methods:Data from 477 DLBCL patients, diagnosed and treated between 2004 and 2013 at two Austrian centres, were evaluated retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 33 publications
(44 reference statements)
2
36
0
1
Order By: Relevance
“…Furthermore, a variety of systemic inflammatory biomarkers has been identified and studied in patients with DLBCL, and might provide useful prognostic information (Table 4). These biomarkers include NLR [30,31], serum LDH [32], serum CRP [33,34], GPS [35,36], serum albumin [37,38], and the peripheral blood absolute lymphocyte and monocyte counts [39]. Troppan et al [30 ]reported that DLBCL patients with an NLR score <4 at diagnosis experienced better OS and disease-free survival than patients with a score of ≥4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a variety of systemic inflammatory biomarkers has been identified and studied in patients with DLBCL, and might provide useful prognostic information (Table 4). These biomarkers include NLR [30,31], serum LDH [32], serum CRP [33,34], GPS [35,36], serum albumin [37,38], and the peripheral blood absolute lymphocyte and monocyte counts [39]. Troppan et al [30 ]reported that DLBCL patients with an NLR score <4 at diagnosis experienced better OS and disease-free survival than patients with a score of ≥4.…”
Section: Discussionmentioning
confidence: 99%
“…We also used the same cutoff value for pretreatment CRP concentration (10 mg/l) to evaluate the prognostic significance, results showed that pretreatment CRP concentration was significantly associated with worse OS and PFS at univariate analysis (P = 0.007, P = 0.001, respectively), CRP concentrations remained an independent predictor of OS and PFS at multivariate analysis (HR = 0.42, P = 0.047; HR = 0.58, P = 0.043, respectively). Although study of prognostic potential of CRP concentrations in patients with DLBCL for the rituximab era was very few, partly studies have been reported about association between CRP concentration and DLBCL before the rituximab era [15,16] or mixed groups of patients with various lymphoma subtypes [17,18]. Troppan KT et al [16] retrospectively reviewed 477 patients with newly diagnosed DLBCL at 2 Austrian centers.…”
Section: Discussionmentioning
confidence: 99%
“…Although study of prognostic potential of CRP concentrations in patients with DLBCL for the rituximab era was very few, partly studies have been reported about association between CRP concentration and DLBCL before the rituximab era [15,16] or mixed groups of patients with various lymphoma subtypes [17,18]. Troppan KT et al [16] retrospectively reviewed 477 patients with newly diagnosed DLBCL at 2 Austrian centers. Increased CRP concentrations were defined as N15 mg/l.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated levels of CRP had been found in patients with cancers [9][10][11][12]15]. Previous studies also showed that elevated levels of CRP were associated with decreased survival and increased risk of mortality in various cancers [16][17][18][19][20][21][22]. However, there are few studies performed to assess the association between CRP levels and prognosis of osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%